2010
DOI: 10.1155/2010/969084
|View full text |Cite
|
Sign up to set email alerts
|

Breast Carcinoma Cells in Primary Tumors and Effusions Have Different Gene Array Profiles

Abstract: The detection of breast carcinoma cells in effusions is associated with rapidly fatal outcome, but these cells are poorly characterized at the molecular level. This study compared the gene array signatures of breast carcinoma cells in primary carcinomas and effusions. The genetic signature of 10 primary tumors and 10 effusions was analyzed using the Array-Ready Oligo set for the Human Genome platform. Results for selected genes were validated using PCR, Western blotting, and immunohistochemistry. Array analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…Despite this heterogeneity, MPE consistently express high levels of metastasis-related proteins, such as ezrin and claudin-4, compared to primary tumors. 34 Culture of MPE cells in the presence of low-passage ASC unequivocally promoted the growth of MPE cells (5.1-fold increase, p ¼ 0.0005) ( Fig. 1; Table 1).…”
Section: Regenerative Therapy After Cancer Surgerymentioning
confidence: 84%
“…Despite this heterogeneity, MPE consistently express high levels of metastasis-related proteins, such as ezrin and claudin-4, compared to primary tumors. 34 Culture of MPE cells in the presence of low-passage ASC unequivocally promoted the growth of MPE cells (5.1-fold increase, p ¼ 0.0005) ( Fig. 1; Table 1).…”
Section: Regenerative Therapy After Cancer Surgerymentioning
confidence: 84%
“…However, although recurrence as metastatic disease is the major cause of tumor-related mortality, the processes which lead to metastasis formation in general and effusion formation in particular, are still incompletely understood. We recently reported that breast carcinoma cells in effusions differ from their counterparts in primary carcinomas mainly in expression of molecules involved in cell-ECM interactions [11]. These molecules may have regulatory effect on cell-cell interactions, survival in the absence of substrate and enhanced cell motility of carcinoma cells, leading to effusion formation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently performed gene array analysis [11], we found that two metastasis-associated genes, the BCAR1 gene encoding p130cas protein and the EZR/VIL2 gene encoding ezrin, are significantly upregulated in breast carcinoma effusions compared to primary carcinomas. We hypothesized that if the upregulation of p130cas and Ezrin is critical for tumor progression, then silencing of their expression in MDA-MB-231 cells will result in a less invasive phenotype and induce differentiation on Matrigel.…”
Section: Expression Of Bcar1/p130cas and Ezr/vil2/ezrin In 3-d Differmentioning
confidence: 98%
See 2 more Smart Citations